THE EFFECT OF BLENDED LEARNING ON EDUCATIONAL ACCOUNTABILITY AND CREATIVITY OF IRANIAN EFL LEARNERS - Fazlali, Fatemeh (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
This study investigates the influence of blended learning instruction (BLI) on the educational accountability and creativity of intermediate EFL learners in Iran. Moreover, it aims to identify EFL learners’ attitudes toward BLI. To this end, 60 female intermediate EFL learners were selected out of 90 through their performance on a sample of the Oxford Quick Placement Test (OQPT). The participants were assigned into two 30-learner groups (i.e., BLI and control). The first questionnaires were administered as their pre-test to check EFL learners’ educational accountability and creativity level before the treatment. During the intervention, the experimental group received instruction through BLI, while the control group received conventional instruction. The second questionnaires were administered as a post-test to check EFL learners’ educational accountability and creativity level after the treatment. Moreover, 10 EFL learners were randomly selected from the BLI group to be interviewed. The results of the two separate ANCOVAs indicated that BLI significantly affected EFL learners’ educational accountability and creativity. The results of the interviews indicated that the majority of the participants believed that BLI made them more self-directed and autonomous. Similarly, 90% of the learners believed that BLI had changed their views towards self and cooperative learning.